Efektivitas Konseling Kelompok Berbasis Islam Untuk Mereduksi Perilaku Mistik Remaja Kecanduan Togel - Syamsul Wahid; Suryati; Lena Marianti (Scidacplus, 2023)
This study entitled the effectiveness of Islamic-based group counseling to reduce the mystical behavior of adolescents addicted to lottery aims to find out how the mystical behavior of adolescents addicted to lottery in Hamlet II, Pulau Gemantung Ilir Village, Kec. Tanjung Lubuk OKI and how is the effectiveness of Islamic-based group counseling to reduce the mystical behavior of adolescents addicted to lottery in Hamlet II, Pulau Gemantung Ilir Village, Kec. Tanjung Lubuk OKI. The research methodology used is quantitative and experimental research. The sample is 5 people. The sampling technique in this study was purposive sampling. This study was designed using the One-Group Pre-test-Post-test Design. Data collection techniques with the questionnaire method. The analysis used in this study was Instrument Test and Hypothesis Test using non-parametric statistical analysis with the Wilcoxon test with SPSS version 25.0. The results showed that the mystical behavior of adolescents addicted to lottery in Dusun II Pulau Gemantung Ilir District, Kec. Tanjung Lubuk OKI which is in the Moderate category with a percentage of 60%. The Wilcoxon test results show that Asymp. Sig (2-tailed) with a sign value = 0.042 <0.05. From the results of this analysis, it can be concluded that ha is accepted and ho is rejected, which means that there is a difference between the pre-test and post-test. It can be concluded that Islamic-based group counseling is effectively used to induce the mystical behavior of adolescents addicted to lottery in Hamlet II, Pulau Gemantung Ilir Village, Sub-district of Tanjung Lubuk OKI.